Analysis of Different Interactive Teaching Methodology - Panda, Dr Subrat; Das, Dr Ananya; Baruah, Dr Surajit Ray; Baruah, Lina (International Journal of Innovative Research in Medical Science, 2020)
Introduction: The interactive teaching system is one such tool which aims at improving the conventional lecture. In this study we had compared three types of interactive teaching viz., flipped class room, MCQ (Multiple Choice Question) based interactive teaching and confusion technique by kircpatrics level 1 evaluation. Methodology: It was an academic study conducted for a period of 1year for final year M.B.B.S students’ batch of 50 in Obstetrics and Gynaecology department of NEIGRIHMS from March 2018 to March 2019. Out of a total of 12 topics selected for interactive teaching technique, 4 topics were taught in flipped classroom technique, another 4 taught with putting MCQ in the class and remaining 4 topics were taught using confusion technique. Immediate feedback was obtained from students using likert chart. All the data were collected and analysed by Wilcoxon Signed rank test by using SPS Software 22. Observation: Flipped classroom technique of teaching was found preferable to MCQ technique (p value<0.01). Also flipped class room technique was preferred by student to confusion technique (p value<0.01). On comparision between MCQ and Confusion technique, MCQ was preferred by the students (p value <0.01). Conclusion: Interactive techniques and strategies make the students actively involved in the learning process, retaining more information and hence leaving them satisfied. In our study, flipped classroom method was the most preferred method by the students as a modality of interactive teaching when compared to MCQ based teaching and Confusion technique.